Breast reconstruction surgery of breast cancer patients. Breast reconstruction surgery of breast cancer patients. - Połom, Karol; Murawa, Dawid; Wasiewicz, Janusz; Połom, Wojciech; Murawa, Paweł (Contemporary Oncology/Współczesna Onkologia, 2009)
Introduction: Breast cancer is still the most common cancer among women in Poland. The basic treatment is surgery of the breast. More and more attention is paid to quality of life of these patients. Every year the number of patients interested in breast conserving treatment and in breast reconstructive surgery increases. Surgery also has much more to offer in this issue of reconstruction. We are able to offer a wide range of different surgical procedures, including breast implants and autologous tissue breast reconstruction. Aim: Review of the literature on breast reconstructive surgery in patients with breast cancer. It compares surgical techniques which use implants or autologous tissues. The authors indicate the advantages and disadvantages of each surgical breast reconstruction method. Conclusion: The number of patients undergoing breast reconstructive surgery is increasing. When choosing the best option for surgery, the patient should be informed about all possibilities of breast reconstruction, advantages and dis-advantages of each technique, and optimal time of reconstruction connected with cancer treatment.